Modelling income processes with lots of heterogeneity. - Browning, M; Ejrnæs, M; Alvarez, J (2010)
All empirical models of earnings processes in the literature assume a good deal of homogeneity. In contrast to this we model earnings processes allowing for lots of heterogeneity between agents. We also introduce an ex- tension to the linear ARMA model that allows that the initial convergence to the long run may be di¤erent from that implied by the conventional ARMA model. This is particularly important for unit root tests which are actually tests of a composite of two independent hypotheses. We …t our models to a variety of statistics including most of those considered by pre- vious investigators. We use a sample drawn from the PSID, and focus on white males with a high school degree. Despite this observable homogene- ity we …nd much greater latent heterogeneity than previous investigators.